2017
DOI: 10.1016/s0140-6736(17)30499-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of subarachnoid haemorrhage Canadian clinical decision rules for investigation of acute headache: a retrospective case note review

Abstract: Background Physicians often face a dilemma to investigate alert and neurologically intact patients presenting with acute headache to emergency departments. Two Canadian prospective cohort studies evaluated high-risk clinical characteristics for subarachnoid haemorrhage in such patients and proposed clinical decision rules (Canadian rules 1, 2, 3, and Ottawa) for investigation of acute headache. We aimed to determine investigation rates for subarachnoid haemorrhage in a cohort of neurologically intact patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…18 Another UK study reported a similar CT investigation rate of 61.7% with the application of the Ottawa SAH rule, which was significantly higher than the rate of 54.2% in actual practice. 19 A review surmised that while the Ottawa SAH rule seemingly can rule out SAH, in actual practice, it might increase the frequency of CT investigations. 11 However, there is still a lack of impact analysis regarding the effects of the Ottawa SAH rule on patients' neurological outcomes and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…18 Another UK study reported a similar CT investigation rate of 61.7% with the application of the Ottawa SAH rule, which was significantly higher than the rate of 54.2% in actual practice. 19 A review surmised that while the Ottawa SAH rule seemingly can rule out SAH, in actual practice, it might increase the frequency of CT investigations. 11 However, there is still a lack of impact analysis regarding the effects of the Ottawa SAH rule on patients' neurological outcomes and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies assessed the clinical decision rules developed by Perry et al for screening patients according to the presence of clinical characteristics associated with a high risk of SAH 13–25. The predecessors of the Ottawa SAH Rule (sometimes termed the ‘Canadian clinical decision rules 1, 2 and 3’) were evaluated in six studies.…”
Section: Resultsmentioning
confidence: 99%
“…The potential impact of the Ottawa rule on neuroimaging rates is analysed in Fig 1. In total, there were eight studies that included rates of CT of the head in the original patient population and the potential rate of CT of the head if the Ottawa rule was applied. This included the external validation studies discussed earlier and two other studies from Matloob et al and Yiangou et al 20,21 These authors analysed an earlier version of the Ottawa rule and so the increase in CT rates in these studies is not exact but indicative only. There was an increase in the need for CT of the head following the application of the Ottawa rule in five of the eight studies, ranging from <1% to 100%.…”
Section: Discussionmentioning
confidence: 99%